ШОИР ҲАМЗАНИНГ СИРЛИ ЎЛИМИГА ОИД МУЛОҲАЗАЛАР (Scientific journal of the Fergana State University, 2023)
In the article on the base of archive documents and materials of periodical press the circumstances of death of famous figure of Uzbek literature of XX th century Khamza Khakimzade are reviewed and new considerations on this subject are given.